Pengaruh Metode Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Mahasiswa pada Materi Reading Comprehension - Silalahi, Dewi Paulina (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
Reading comprehension is the ability to understand, analyze, and interpret the information contained in written texts. Innovative and student-centered teaching methods, such as discovery learning, are needed. Discovery learning is a student-centered learning method where students actively engage in the process of discovering concepts or understanding through exploration, experimentation, and problem-solving. This research employs the Classroom Action Research method, with 40 students as subjects. The implementation is carried out in two cycles consisting of planning, action, observation, and reflection phases. The results of the study show that in the first cycle, the average score of students was 69.1, with a graduation rate of 60%, indicating a need for improvement in the learning process. After implementing improvement strategies in the second cycle, the average score increased to 87.4, with a graduation rate reaching 90%. Thus, the application of the discovery learning method significantly enhances students' reading comprehension skills.